Keragaman Tumbuhan Paku (Pteridophyta) di Taman Biodiversitas Hutan Hujan Tropis Mandiangin - Abdul Majid; Aulia Ajizah; Sri Amintarti (Universitas Al Azhar Indonesia, 2022)
Ferns are generally found in high humidity habitats. Mandiangin Tropical Rain Forest Biodiversity Park has high rainfall and humadity, so it has the potential as a habitat for ferns. Research has been carried out that aims to inventory and describe the diversity of ferns found in the Mandiangin Tropicaal Rain Forest Biodiversity Park. The data were obtained by purposive sampling by circling the Mandiangin Tropical Rain Forest Biodiversity Park. The result showed that 11 families with 15 species of ferns were found, namely Drynaria sparsisora, Gleichenia linearis, Christella Sp, Christella dentata, Microlepia speluncae, Nephrolepis falcata, Pteris biaurita, Pithyrogamma calomelanos, Davalia dentriculata, Pteris sp, Platycerium bifurcatum, Selaginela Sp, Lygodium sp., Asplenium nidus and Pleocnemia irregularis.Keywords - Ferns (Pteridophyta), Mandiangin Tropicaal Rain Forest Biodiversity Park South Borneo, Manjai Hill Valley